Penerapan Teori Emotional Design pada Karya Mahasiswa dalam Mata Kuliah Psikologi Desain: Analisis Estetika, Fungsi, dan Pengalaman Pengguna - Wardhani, Krishna; Fitriyyah, Nurfadilah; Nurjamilah, Siti; Rachman, Rizki Maulana (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
In the Design Psychology course, the application of Don Norman’s Emotional Design theory by students is often limited to visual or visceral aspects, while the behavioral and reflective levels remain underdeveloped. This study aims to examine the implementation of Emotional Design in interdisciplinary student projects and to identify the challenges emerging within collaborative learning contexts. A qualitative case study approach was employed, based on the observation and analysis of design works produced by three interdisciplinary student groups in the Design Psychology course at Sekolah Tinggi Desain Indonesia. The findings indicate that students’ works tend to emphasize visceral and behavioral aspects, whereas the reflective level appears in a limited and symbolic manner, influenced by disciplinary backgrounds and group dynamics. Based on these findings, this study proposes a sprint-based pedagogical model that integrates visceral, behavioral, and reflective stages progressively within a single-semester learning cycle. The proposed model is intended to provide a more structured space for reflection and to support the development of collective emotional meaning in interdisciplinary Emotional Design education.